(3LQjeI JgQjH GdegGLQjf (B:s "(3OQGSI ebGQfI(B" /s - (3SYjO, eMeO UHGMs ((3GdbGgQI (B:s (3GdeQcR GdYQHj ddOQGSGJ hGdHMhK GdYdejI ddfTQ hGdJhRjY,s, 2018)
(3JhUd GdeLJeY GdOhdj HYO cOM Whjd hTGb hHPd GdYOjO ef GdLghO Edi UjGZI fUhU OhdjI JVef aQV YbhHGJ Ydi GdeSDhdjf Yf YedjGJ GdJgQjH hGdPjf jQJcHhf GdCaYGd GdJj JDOj Edi EONGd Ch ENQGL GdCTNGU Edi CbGdje GdOhd Ch GdJj Jecfge ef GdHbGA ajgG Ydi fMh ZjQ eTQhY(B. (3dPG Sha JfUH gPg GdOQGSI Ydi GdLGfH GdbGfhfj ddehVhY(B. (3aYdi GdQZe ef bjGe GdYOjO ef GdOhd HGdJhbjY Ydi fUhU GdHQhJhchd GdOhdj GdNGU HecGaMI JgQjH GdegGLQjf Yf WQjb GdHQ hGdHMQ hGdLh Gdeced dGJaGbjI GdCee GdeJMOI decGaMI GdLQjeI GdefXeI YHQ GdhWfjI, heUGObI GdYOjO efgG Ydi gPg GdfUhU, hef HjfgG GdYQGb, EdG Cfg dG jRGd jhLO fbU cHjQ aj GdJYGed GdbGfhfj eY gPg GdXGgQI(B. (3EP Cf ZGdHjI gPg GdOhd hdMO GdBf de JZjQ ef JTQjYGJgG GdYbGHjI dcj JfSLe eY fUhU gPG GdHQhJhchd hJeGQS HGdJGdj EecGfjI eYGbHI GdeSDhdjf Yf GQJcGHgG(B. (3hfXQG dGfOQGL LQjeI JgQjH GdegGLQjf Vef WGFaI GdLQGFe GdYGHQI ddMOhO GdJj dG JbJUQ BKGQgG Ydi MOhO OhdI hGMOI, hdchfgG JTcd NWhQI Ydi GdeUGdM GdJj Jge GdeLJeY GdEfSGfj Ydi MO ShGA ; dPG aEf GdefgLjI GdYdejI JJWdH OQGSI gPg GdLQjeI aj HYOjgG GdOhdj hGdhWfj(B.s
(3GdeMJhjGJ (B: (3GdaUd GdChd (B: (3eGgjI LQjeI JgQjH GdegGLQjf, GdeHMK GdChd (B: (3Mhd GdgLQI hJgQjH GdegGLQjf (B...-(3GdaUd GdKGfj (B: (3CQcGf LQjeI JgQjH GdegGLQjf, GdeHMK GdChd (B: (3UaI GdTNU GdegQH, GdeWdH GdChd (B: (3Cf jchf GdTNU GdegQH EfSGfG (B...-(3GdaUd GdKGdK (B: (3GdBKGQ GdbGfhfjI dLQjeI JgQjH GdegGLQjf, GdeHMK GdChd (B: (3GdBKGQ GdLRGFjI (B... (3hehVhYGJ CNQi(B.s
(3HHdjhLQGajI (B: (3UaMI (B349-373.s
(3ebQQGJ OQGSjI dWdGH GdLGeYI (B2024.s
Keywords: (3GdgLQI ZjQ GdTQYjI (B((3bGfhf Ohdj(B)s